Molecular Typing of Multiple Isolates Is Essential to Diagnose Cutibacterium acnes Orthopedic Device–related Infection. (8th November 2018) - El Sayed, Faten; Roux, Anne-Laure; Sapriel, Guillaume; Salomon, Elsa; Bauer, Thomas; Gaillard, Jean-Louis; Rottman, Martin
Abstract: Cutibacterium acnes orthopedic device–related infections (ODRIs) range from obvious infections to solely culture-based diagnoses. Multilocus sequence typing of multiple isolates from the same procedure revealed that most cases with normal C-reactive protein levels that were classified as C. acnes ODRI would be considered contaminations when accounting for genotypic data.